MENYIAPKAN RUANGAN DIKLAT SEBAGAI SUMBER BELAJAR YANG KONDUSIF - Estu Miyarso (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Place or training room have some functions among others as facilities andbasic facilities or facility, source of learning, centre of activities, andbarometer assess presstige organizer of training. Management of trainingplace cover planning activity, organizational, execution, and monitoring.Some training room criteria which must be paid attention for example;Accesible Comfortable, Quite, private, free and, Space in Around easilymove to trainees for Sufficient also have some nature of becomingconditions that is; flexible, isolasif or free from various trouble, settlementof enough light, and existence of adequate ventilation. Arrangement ofclass room and seating room influence the way discussion, and in turninfluence also leadership pattern appearance in group able to streamlineresult of from target learn or target of training broaderly.